'Unionisation' of the European Court of Human Rights' ne bis in idem jurisprudence: the Case of Mihalache v Romania. Issue 2 (June 2020) - Serneels, Cedric
This article analyses the decision of the European Court of Human Rights (ECtHR) in the case of Mihalache v Romania . In the judgment, the Court, dealing with the application of the ne bis in idem principle, further elaborates on the different components of the concept 'final acquittal or conviction' under Article 4 of Protocol No 7 to the European Convention on Human Rights. The author studies this aspect of the ruling through the lens of judicial dialogue and examines in particular the influence of relevant case law of the Court of Justice of the European Union on the ECtHR's reasoning.